Analysis of Cancer Control Policies in Surakarta - Prasetya, Hanung; Setyawan, Dodiet Aditya; Sudiro, Sudiro; Utomo, Budi; Mirshanti, Farahdila; Azmiardi, Akhmad (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2024)
Background:Cancer is the main cause of death throughout the world. Cervical cancer causes 7.5% of women's deaths, 85% of which occur in developing countries. According to the latest data fromGlobocan for 2020, there were 141.1 new cancer cases per 100,000 people in Indonesia, and there were 85.1 cancer deaths per 100,000 people. Cancer is the largest cause of death from non-communicable diseases, second only to cardiovascular disease (heart and blood vessels). Subjects and Methods:This research uses a qualitative descriptive method. Analysis is carried out using data that comes from various sources, not just one source, through interviews and documentation. The location chosen was Surakarta City. This research is public policy research. Policy research is research relating to the formulation and formulation of policies, policy implementation, policy performance and the policy environment. Results:In general, there are policies that regulate the control of cancer. In general, everyone has implemented cancer control through promotive, preventive and curative efforts. There needs to be support from multi-sectors in controlling cancer. Conclusion:There is a need for policy outreach and the role of multisectors/multiactors in cancer control policies in Surakarta, assistance to the community and the role of universities in controlling cancer, the importance of creating an institution that specifically handles cancer control and the importance of advocacy and education about cancer control to the community and psychoeducation for families who have a family member with cancer. Keywords:Policy Analysis, Control, Cancer